ANALYSIS OF THE TEACHER PERFORMANCE EFFECTIVENESS IN THE CONTEXT OF ORGANIZATIONAL CULTURE - Fradito, Aditia; Buana, Arum Sekar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the last few decades, there has been numerous studies on the effect of organizational culture to increase work performance, as well as organizational citizen behavior to increase effectiveness of the organization. The performance of teacher is heavily influenced by several factors such as motivation, leadership, organizational culture, organizational citizen behavior and others. This research was aimed to test the effect of organizational culture to State Madrasa teacher performance in Pesawaran Regency. This research used quantitative design. The data were collected through questionnaire shared via Google Forms to 148 respondents from the total of 222 people. The result showed that variable of organizational culture positively affected teacher performance. Coefficient of determination was 0.493 or 49.3% for the variable of organizational culture was influenced by other factors that were not studied in this research. Based on the partial test result, the variable on organizational culture had the significant value of 0.029 < 0.05